2021
DOI: 10.1108/rausp-08-2019-0176
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dynamic capabilities on startup growth

Abstract: Purpose The purpose of this study is to analyze the relationship between dynamic service innovation capabilities (DSICs) and startup growth in an emerging country. Design/methodology/approach This paper used a theoretical DSIC model to process data on 137 Brazilian startups, using a stepwise regression. Findings Service startup growth is related to the capability of enterprises to understand market signals, learn from customers and design a scalable, repetitive and profitable business model. Research lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 101 publications
(153 reference statements)
0
7
0
Order By: Relevance
“…This building of dynamic capabilities creates and organizes an organizational structure to allow searching and testing newness as of initial vision of founders (Oliva et al , 2019). In addition, exploiting new opportunities under a highly uncertain market environment (Giardino et al , 2014), the presence of dynamic capabilities for startups are crucial in enabling a rapid development and/or reconfiguration of resources for value creation as a sustainable basis to survive (Wu, 2007; Feng et al , 2019; Oliva et al , 2019; Ma et al , 2020; Teixeira et al , 2021).…”
Section: Literature Review On Startups’ Survival and Dynamic Capabili...mentioning
confidence: 99%
See 1 more Smart Citation
“…This building of dynamic capabilities creates and organizes an organizational structure to allow searching and testing newness as of initial vision of founders (Oliva et al , 2019). In addition, exploiting new opportunities under a highly uncertain market environment (Giardino et al , 2014), the presence of dynamic capabilities for startups are crucial in enabling a rapid development and/or reconfiguration of resources for value creation as a sustainable basis to survive (Wu, 2007; Feng et al , 2019; Oliva et al , 2019; Ma et al , 2020; Teixeira et al , 2021).…”
Section: Literature Review On Startups’ Survival and Dynamic Capabili...mentioning
confidence: 99%
“…From a research standpoint about dynamic capabilities of startups (Thiele and Fellnhofer, 2015; Chin et al , 2016; Datta et al , 2018; Caseiro and Coelho, 2019; Dong, 2019; Feng et al , 2019; Ma et al , 2020; Polo García-Ochoa et al , 2020; Steiber and Alänge, 2020; Guo et al , 2021; Teixeira et al , 2021), internal and external forces affect business in general (Cavalcante et al , 2011; Chesbrough, 2010; de Reuver et al , 2009; Johnson et al , 2008; Pucihar et al , 2019; Rub et al , 2017; Saebi, 2015; Seo and Lee, 2019; Teece, 2007; Thiele and Fellnhofer, 2015; Van Den Heuvel et al , 2020), and considering the differences in capabilities from startups to handle environmental changes, our framework combines dynamic capabilities of startups within their effects on tangible and intangible resources exchange to overcome challenges imposed from internal and external forces.…”
Section: Building a Base Of Dynamic Capabilities Of Startupsmentioning
confidence: 99%
“…Not only the use of dynamic capabilities, but the characteristics of the given capabilities can also cause a difference: dynamic capabilities have an indirect effect on performance [Shi -Yuan -Lee, 2022], but this effect on performance can be influenced by participation in an acceleration program [García-Ochoa -De-Pablos-Heredero -Jimenez, 2022]. Among start-ups, it is not (only) technological (dynamic) capabilities that determine the growth of the firm, but rather, the ability to learn from customers and create scalable, repeatable and profitable business models [Teixeira -de Moura -Lopes -Marconatto -Fischmann, 2021]. Young and smaller organizations generally behave in the same way in terms of dynamic capabilities.…”
Section: Articlesmentioning
confidence: 99%
“…Furthermore, the logistics industry is characterized by high uncertainty and, therefore, for startups to compete in this highly dynamic environment, they must develop dynamic capabilities. In this sense, previous studies have shown that the ability to identify customer needs is essential for the startups' growth (Teixeira et al, 2021). Previous research has also revealed that companies must align customer needs with the requirements of sustainable development, taking a proactive role in creating sustainable behavior (Inigo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the logistics industry is characterized by high uncertainty and, therefore, for startups to compete in this highly dynamic environment, they must develop dynamic capabilities. In this sense, previous studies have shown that the ability to identify customer needs is essential for the startups' growth (Teixeira et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%